POLA KOMUNIKASI KELOMPOK KOMUNITAS ANGKUTAN AIR PADA BANTARAN SUNGAI MUSI– PALEMBANG - Adli; Lovia Evanne; Leti Karmila; Dendi (Jurnal Ilmu Komunikasi Balayudha, 2021)
River transportation in South Sumatra has a very long history. Long before independence, the Musi river flow had become an important part of the economic development journey of the people of South Sumatra. This sector is a medium for social and economic growth for the South Sumatra region. Currently, this transportation is still running as usual although the number continues to decline, but this is still a job opportunity to help the community's economy. This study uses a qualitative method with a descriptive approach to analyze the research results. Sources of information (informants) in this study were business actors involved in river transport communities who were randomly selected to determine the communication patterns of river transport community groups on the banks of the Musi River and useful for researchers in the field of group communication and development communication. The results showed that the communication pattern that occurred in the river transportation community in the form of capital expressed by newcomb where the communicator and the communicant exchanged roles in discussing one focus of the problem. Another finding is that government communication to the river transport community is still in the form of policy socialization and is top-down in nature.